Positive electrode active material, method for preparing same, positive electrode, and rechargeable lithium battery

A lithium nickel manganese aluminum composite oxide with a uniform aluminum coating addresses the cobalt scarcity issue, ensuring high capacity, efficiency, and long cycle life in rechargeable lithium batteries.

CN119133377APending Publication Date: 2024-12-13SAMSUNG SDI CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410751769.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-06-12
Filing Date
2024-06-12
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The increasing demand for rechargeable lithium batteries with high energy density and capacity is hindered by the limited supply and high cost of cobalt, necessitating the development of cobalt-free or low-cobalt positive electrode active materials that maintain structural stability and cycle life characteristics, especially under high voltage and high temperature conditions.

Method used

A lithium nickel manganese aluminum composite oxide is used as the core particle, coated with a thin and uniform aluminum layer to enhance structural stability and minimize production costs, while maintaining high capacity and efficiency.

Benefits of technology

The composite oxide achieves high initial charge and discharge capacity, efficiency, and long cycle life characteristics under high voltage and temperature conditions by inhibiting side reactions with the electrolyte and reducing gas generation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133377A_ABST
    Figure CN119133377A_ABST
Patent Text Reader

Abstract

The invention relates to a positive electrode active material, a method for preparing the same, a positive electrode, and a rechargeable lithium battery. A positive electrode active material of a rechargeable lithium battery may include a core particle including a lithium nickel manganese aluminum-based composite oxide, and a coating layer disposed on a surface of the core particle and including aluminum, a nickel content of the core particle is about 60 mol% to about 80 mol% and an aluminum content of the core particle is about 1 mol% to about 3 mol%, and an aluminum content of the coating layer is about 0.1 mol% to about 2 mol% based on about 100 mol% of a total metal other than lithium in the positive electrode active material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] Embodiments of the present disclosure described herein relate to a positive electrode active material, a method of preparing the same, a positive electrode including the positive electrode active material, and a rechargeable lithium battery. Background Art

[0002] Portable information devices (such as cellular phones, laptop computers, smart phones, etc.) or vehicles (e.g., hybrid vehicles or electric vehicles) have used rechargeable lithium batteries with relatively high energy density and relative portability as driving power sources. Recently, research has been actively conducted to use rechargeable lithium batteries with relatively high energy density as driving power sources or energy storage power sources (e.g., power walls) of vehicles (e.g., hybrid vehicles or electric vehicles).

[0003] In order to implement rechargeable lithium batteries suitable for these purposes, one or more suitable positive electrode active materials are being studied. Among them, lithium nickel oxides, lithium nickel manganese cobalt composite oxides, lithium nickel cobalt aluminum composite oxides, lithium cobalt oxides, etc. are mainly used as positive electrode active materials. However, despite the recent rapid increase in demand or expectation for rechargeable lithium batteries with relatively large size, relatively high capacity and / or relatively high energy density, the supply of cobalt (rare metal) positive electrode active materials may be insufficient. In other words, because cobalt is expensive and there is not much cobalt reserves, it is necessary or desirable to develop a positive electrode active material that excludes cobalt or includes cobalt in a reduced content (e.g., amount). Summary of the invention

[0004] Aspects according to one or more embodiments relate to a positive electrode active material including a lithium nickel manganese aluminum composite oxide, a preparation method thereof, and a positive electrode and a rechargeable lithium battery including the same, the positive electrode active material ensuring economic efficiency, relatively high capacity and / or relatively long cycle life characteristics, and having improved high voltage and high temperature characteristics.

[0005] Aspects according to one or more embodiments relate to a positive electrode active material that maximizes or increases capacity while minimizing or reducing production costs, ensures long cycle life, and improves high voltage and high temperature characteristics. A rechargeable lithium battery using the positive electrode active material can exhibit relatively high initial charge capacity / initial discharge capacity and initial efficiency even under high voltage operating conditions, and can achieve long cycle life characteristics.

[0006] Additional aspects will be set forth in part in the description which follows and, in part, will be obvious from the description, or may be learned by practice of the presented embodiments of the disclosure.

[0007] According to one or more embodiments, the positive electrode active material includes: a core particle including a lithium nickel manganese aluminum composite oxide, and a coating disposed on the surface of the core particle and including aluminum, wherein the nickel content (e.g., amount) of the core particle is about 60 mol% to about 80 mol% and the aluminum content (e.g., amount) of the core particle is about 1 mol% to about 3 mol% based on 100 mol% of the total metal other than lithium in the positive electrode active material, and the aluminum content (e.g., amount) of the coating is about 0.1 mol% to about 2 mol% based on 100 mol% of the total metal other than lithium in the positive electrode active material.

[0008] According to one or more embodiments, a method for preparing a positive electrode active material includes mixing a nickel-manganese-aluminum composite hydroxide and a lithium raw material and performing a first heat treatment to obtain a lithium-nickel-manganese-aluminum composite oxide, and adding the obtained lithium-nickel-manganese-aluminum composite oxide to a solution of an aqueous solvent of an aluminum raw material and mixing it with a solution of an aqueous solvent of the aluminum raw material, drying and performing a second heat treatment to obtain a positive electrode active material, wherein the nickel content (e.g., amount) is about 60 mol% to about 80 mol% and the aluminum content (e.g., amount) is about 1 mol% to about 3 mol% based on 100 mol% of the total metals other than lithium in the nickel-manganese-aluminum composite hydroxide, and the aluminum content (e.g., amount) in the aluminum raw material is about 0.1 mol% to about 2 mol% based on 100 mol% of the total metals other than lithium in the positive electrode active material.

[0009] According to one or more embodiments, the positive electrode includes a positive electrode current collector and a positive electrode active material layer on the positive electrode current collector, wherein the positive electrode active material layer includes the aforementioned positive electrode active material.

[0010] According to one or more embodiments, a rechargeable lithium battery includes a positive electrode, a negative electrode, and an electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] The accompanying drawings are included to provide a further understanding of the present disclosure and are incorporated into and constitute a part of this specification. The accompanying drawings illustrate example embodiments of the present disclosure and, together with the description, serve to explain the principles of the present disclosure. The above and other aspects, features and advantages of certain embodiments of the present disclosure will become more apparent from the following description taken in conjunction with the accompanying drawings, in which:

[0012] Figure 1 is a perspective view schematically illustrating a rechargeable lithium battery according to some embodiments.

[0013] Figure 2 This is a scanning electron microscope (SEM) image of the positive electrode active material of Comparative Example 1.

[0014] Figure 3 This is a SEM image of the positive electrode active material of Comparative Example 2.

[0015] Figure 4 This is a SEM-EDS (scanning electron microscope-electron dispersive X-ray spectroscopy) image of a cross section of the positive electrode active material of Example 1.

[0016] Figure 5 This is a SEM-EDS image of a cross section of the positive electrode active material of Example 2.

[0017] Figure 6 This is a SEM-EDS image of a cross section of the positive electrode active material of Example 3.

[0018] Figure 7 This is a SEM-EDS image of a cross section of the positive electrode active material of Example 4.

[0019] Figure 8 This is a SEM-EDS image of a cross section of the positive electrode active material of Comparative Example 3.

[0020] Fig. 9 This is a SEM-EDS image of a cross section of the positive electrode active material of Comparative Example 5.

[0021] Fig.10 This is a SEM image of the surface of the positive electrode active material of Comparative Example 5.

[0022] Fig.11 This is a TOF-SIMS (time-of-flight secondary ion mass spectrometry) depth distribution diagram of the positive electrode active material of Example 1.

[0023] Fig.12 This is a transmission electron microscope (TEM) image of a cross section of the positive electrode active material of Example 1.

[0024] Fig.13 for Fig.12 Magnified TEM image of the portion indicated by the rectangle.

[0025] Fig.14 To pass Fig.13 An image obtained by EDS analysis of a TEM image, highlighting O, Al, Mn and Ni from the left.

[0026] Fig.15 To show the contents of O, Al, Mn and Ni Fig.13 and Fig.14 The changes in the direction of the arrows are shown in the EDS line profile.

[0027] Fig.16TEM image and TEM-EDS analysis image of the cross section of the positive electrode active material of Example 1.

[0028] Fig.17 To show the contents of O, Al, Mn and Ni Fig.16 The EDS line profiles showing the changes in the direction of the arrows.

[0029] Fig.18 This is a TEM image of a cross section of the positive electrode active material of Example 1.

[0030] Fig.19 for Fig.18 A magnified image of area 1 (left) and an image highlighting aluminum by EDS analysis (right).

[0031] Fig. 20 for Fig.18 Magnified image of area 2 (left) and EDS analysis image (right).

[0032] Fig.21 for Fig.18 Magnified image of area 3 (left) and EDS analysis image (right).

[0033] Fig. 22 TEM-EDS image showing an enlarged analysis of primary particles in the outermost layer of secondary particles in a cross section of the positive electrode active material of Example 1.

[0034] Fig.23 Reason Fig. 22 TEM images of the parts indicated by arrows ① to ⑥ in FIG.

[0035] Description of Reference Numerals

[0036] 100: Rechargeable lithium battery 10: Positive electrode

[0037] 20: Negative electrode 30: Separator

[0038] 40: electrode assembly 50: shell DETAILED DESCRIPTION

[0039] Hereinafter, specific embodiments will be described in more detail so that those skilled in the art can easily implement them. However, the present disclosure may be embodied in many different forms and is not to be construed as limited to the example embodiments set forth herein.

[0040] The terms utilized herein are only used to describe the embodiments and are not intended to limit the present disclosure. Unless the context clearly indicates otherwise, a singular expression also includes a plural expression.

[0041] As utilized herein, "combinations thereof" refers to mixtures, laminates, composites, copolymers, alloys, blends, reaction products, and the like, of the components.

[0042] In this document, it should be understood that terms such as "comprising", "including" or "having" are intended to mark the presence of specified features, quantities, steps, elements or combinations thereof, but do not exclude the possibility of the presence or addition of one or more other features, quantities, steps, elements or combinations thereof.

[0043] As used herein, expressions such as "at least one of," "one of," and "selected from," when preceding / following a list of elements, modify the entire list of elements and do not modify the individual elements of the list. For example, "at least one selected from a, b, and c" and the like may indicate only a, only b, only c, both a and b (e.g., both a and b), both a and c (e.g., both a and c), both b and c (e.g., both b and c), all of a, b, and c, or variations thereof.

[0044] In the accompanying drawings, for the sake of clarity, the thickness of layers, films, panels, regions, etc. is exaggerated, and the same reference numerals are used throughout to mark the same elements, and repeated descriptions thereof may not be provided in the specification. It will be understood that when an element (such as a layer, film, region, or substrate) is referred to as being "on" another element (such as a layer, film, region, or substrate), it may be directly on the other element (such as a layer, film, region, or substrate) or there may also be intervening elements (such as layers, films, regions, or substrates). In contrast, when an element (such as a layer, film, region, or substrate) is referred to as being "directly on" another element (such as a layer, film, region, or substrate), there are no intervening elements (such as layers, films, regions, or substrates).

[0045] In some embodiments, the “layer” herein includes not only a shape formed on the entire surface when viewed from a plan view but also a shape formed on a partial surface.

[0046] "Group" refers to a Group of the Periodic Table of the Elements according to the International Union of Pure and Applied Chemistry ("IUPAC") Group 1-18 grouping system.

[0047] The average particle size can be measured by a method suitable for those skilled in the art, for example, by a particle size analyzer, or by a transmission electron microscope image or a scanning electron microscope image. In some embodiments, the average particle size value can be obtained by measuring using a dynamic light scattering method, performing data analysis, counting the number of particles in each particle size range, and calculating therefrom. Unless otherwise specified, the average particle size (D50) may refer to the diameter of particles with a cumulative volume of 50% by volume in a particle size distribution. The average particle size (D50) refers to the diameter of particles with a cumulative volume of 50% by volume in a particle size distribution obtained by randomly measuring the size (diameter or major axis length) of about 20 particles in a scanning electron microscope image.

[0048] In this document, “or” is not interpreted as being exclusive. For example, “A or B” is interpreted as including A, B, A+B, etc.

[0049] The term "metal" is interpreted as a concept including common metals, transition metals, and metalloids (semimetals).

[0050] As utilized herein, the term "substantially" and similar terms are used as terms of approximation and not as terms of degree, and are intended to take into account the inherent variations in measured or calculated values ​​that one of ordinary skill in the art would recognize. Also, the term "about" and similar terms, when utilized herein in conjunction with a numerical value or range of values, include the recited value and values ​​within an acceptable range of deviations of the particular value determined by one of ordinary skill in the art taking into account the measurement in question and the errors associated with the measurement of the particular quantity (e.g., limitations of the measurement system). For example, "about" can mean within one or more standard deviations of the recited value, or within ±30%, ±20%, ±10%, or ±5% of the recited value.

[0051] Furthermore, any numerical range set forth in this article is intended to include all sub-ranges of the same numerical precision falling within the range set forth. For example, the range of "1.0 to 10.0" is intended to be included between the minimum value of 1.0 set forth and the maximum value of 10.0 set forth (and including 1.0 and 10.0), that is, all sub-ranges having a minimum value equal to or greater than 1.0 and a maximum value equal to or less than 10.0, such as, for example, 2.4 to 7.6. Any maximum numerical limit set forth in this article is intended to include all lower numerical limits falling therein, and any minimum numerical limit set forth in this specification is intended to include all higher numerical limits falling therein. Accordingly, the applicant reserves the right to modify this specification (including claims) to explicitly set forth any sub-range falling within the range explicitly set forth in this article.

[0052] Hereinafter, a positive electrode active material and a rechargeable lithium battery according to example embodiments will be described in more detail.

[0053] Positive electrode active material

[0054] In some embodiments, the positive electrode active material includes: a core particle including a lithium nickel manganese aluminum composite oxide, and a coating disposed on the surface of the core particle and including aluminum, wherein the nickel content (e.g., amount) of the core particle is about 60 mol% to about 80 mol% and the aluminum content (e.g., amount) of the core particle is about 1 mol% to about 3 mol% based on about 100 mol% of the total metal other than lithium in the positive electrode active material, and the aluminum content (e.g., amount) of the coating is about 0.1 mol% to about 2 mol% based on about 100 mol% of the total metal other than lithium in the positive electrode active material.

[0055] As the price of rare metal cobalt rises sharply, it is necessary to develop positive electrode active materials that exclude cobalt or reduce its content (e.g., amount). Among them, positive electrode active materials with olivine crystal structures (such as lithium iron phosphate (LFP), lithium manganese phosphate (LMP) and / or lithium manganese iron phosphate (LMFP)) or spinel crystal structures (such as lithium manganese oxide (LMO)) are limited in achieving high capacity, because the amount of lithium available in these structures is small. Due to the high lithium availability in the structure of the layered nickel manganese positive electrode active material, the layered nickel manganese positive electrode active material has excellent or appropriate capacity and efficiency characteristics, making it suitable as a material for high-capacity batteries. However, with the removal of cobalt, which plays a key role in the layered structure, the structural stability is reduced, the resistance is increased, and it becomes difficult to ensure long cycle life characteristics. In some embodiments, when cobalt is excluded (e.g., if cobalt is excluded), the problem is that under high voltage and high temperature conditions, the side reaction between the positive electrode active material and the electrolyte is accelerated, thereby increasing the amount of generated gas and deteriorating the cycle life characteristics.

[0056] In some embodiments, aluminum is introduced into the base material, and a lithium nickel manganese aluminum composite oxide is used as a core particle to improve structural stability and minimize or reduce production costs. In some embodiments, a positive electrode active material is proposed, which is coated with a certain amount of aluminum by a specific method to form a substantially uniform coating, thereby maximizing or increasing capacity and initial efficiency, and even under high voltage or high temperature conditions, long cycle life characteristics can be achieved by reducing gas generation.

[0057] Nuclear particles

[0058] The core particles include a lithium nickel manganese aluminum based composite oxide.

[0059] Based on the total metal other than about 100mol% of lithium in the positive electrode active material, the nickel content (e.g., amount) satisfies about 60mol% to about 80mol%. Nickel is contained in the core particles, but can move to some coatings during the coating process. Therefore, the nickel content (e.g., amount) may refer to the nickel content (e.g., amount) contained in the entire positive electrode active material. Based on the total metal other than 100mol% of lithium in the positive electrode active material, the nickel content (e.g., amount) may be, for example, about 65mol% to about 80mol%, about 70mol% to about 80mol%, about 60mol% to about 79mol%, about 60mol% to about 78mol% or about 60mol% to about 75mol%. When the nickel content (e.g., amount) satisfies the above range, even if the cobalt content (e.g., amount) is reduced (e.g., when the cobalt content (e.g., amount) is reduced), high capacity can be achieved and structural stability can be increased.

[0060] These lithium nickel manganese aluminum composite oxides are different from high nickel composite oxides having a nickel content (e.g., amount) exceeding about 80 mol%. According to some embodiments, the positive electrode active material having a nickel content (e.g., amount) of about 60 mol% to about 80 mol% is different from high nickel composite oxides in terms of residual lithium content (e.g., amount) on the surface, surface pH conditions, surface shape, etc., and therefore the same coating method cannot be applied, and the performance and application fields are different.

[0061] For example, based on the total metal other than about 100mol% of lithium in the positive electrode active material, the manganese content (e.g., amount) may be about 10mol% to about 39mol%, about 10mol% to about 35mol%, about 10mol% to about 30mol%, about 10mol% to about 29mol%, about 15mol% to about 39mol%, about 20mol% to about 39mol% or about 20mol% to about 30mol%. Manganese is contained in the core particles, but can move to some coatings during the coating process, so the manganese content (e.g., amount) may refer to the manganese content (e.g., amount) contained in the entire positive electrode active material. When the manganese content (e.g., amount) meets the above range, the positive electrode active material can improve structural stability while achieving high capacity.

[0062] Based on the total metal other than about 100mol% of lithium in the positive electrode active material, the aluminum content (e.g., amount) in the core particle may be about 1mol% to about 3mol%, such as about 1mol% to about 2.5mol%, about 1mol% to about 2mol% or about 1mol% to about 1.9mol%. In this article, the aluminum content (e.g., amount) of the core particle refers to the content (e.g., amount) of aluminum present in the core particle. If the aluminum content (e.g., amount) of the core particle meets the above range (e.g., when the aluminum content (e.g., amount) of the core particle meets the above range), even if cobalt is excluded from the core particle (e.g., when cobalt is excluded from the core particle), a stable layered structure can be maintained, the problem of structural collapse caused by charging and discharging can be suppressed or reduced, and the long cycle life characteristics of the positive electrode active material can be achieved.

[0063] According to some embodiments, the concentration of aluminum in the core particles may be substantially uniform. In other words, it refers to the absence of an aluminum concentration gradient from the center to the surface in the core particles, or the aluminum concentration outside the core particles is neither higher than nor lower than the aluminum concentration inside the core particles, and the aluminum is uniformly distributed in the core particles. This can be regarded as a structure obtained by synthesizing a composite oxide using a nickel-manganese-aluminum hydroxide as a precursor, wherein an aluminum-containing compound is used during the preparation of the precursor, and aluminum is not additionally doped during the synthesis of the core particles. The core particles may be in the form of secondary particles in which a plurality of primary particles are aggregated, and the aluminum content (e.g., amount) inside the primary particles may be regarded as the same or similar regardless of the position of the primary particles. In other words, if a primary particle is selected at a random position in the cross section of the secondary particle, and the aluminum content (e.g., amount) is measured inside the primary particle rather than at the interface (e.g., when a primary particle is selected at a random position in the cross section of the secondary particle, and the aluminum content (e.g., amount) is measured inside the primary particle rather than at the interface), regardless of the position of the primary particle, that is, regardless of whether the primary particle is close to the center of the secondary particle or close to the surface of the secondary particle, the aluminum content (e.g., amount) can be expressed as the same / similar / substantially uniform. In this structure, even if cobalt is not present or is present in a very small amount (e.g., when cobalt is not present or is present in a very small amount), a stable layered structure can be maintained, and aluminum byproducts or aluminum aggregates are not generated, so the capacity, initial efficiency and cycle life characteristics of the positive electrode active material can be improved at the same time.

[0064] For example, the lithium nickel manganese aluminum-based composite oxide may be represented by Chemical Formula 1.

[0065] Chemical formula 1

[0066] Li a1 Ni x1 Mn y1 Al z1 M 1 w1O 2-b1 X b1 ,

[0067] In Chemical Formula 1, 0.9≤a1≤1.8, 0.6≤x1≤0.8, 0.1≤y1≤0.39, 0.01<z1≤0.03, 0≤w1≤0.29, 0.9≤x1+y1+z1+w1≤1.1, and 0≤b1≤0.1, M 1 is one or more elements selected from B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W and Zr, and X is one or more elements selected from F, P and S.

[0068] In Chemical Formula 1, 0.9≤a1≤1.5 or 0.9≤a1≤1.2. In some embodiments, 0.6≤x1≤0.79, 0.6≤x1≤0.78, 0.6≤x1≤0.75, 0.65≤x1≤0.8 or 0.7≤x1≤0.79; 0.1≤y1≤0.35, 0.1≤y1≤0.30, 0.1≤y1≤0.29, 0.15≤y1≤0.39 or 0.2≤y1≤0.3; 0.01<z1≤0.025, 0 .01<z1≤0.02 or 0.01<z1≤0.019; 0≤w1≤0.28, 0≤w1≤0.27, 0≤w1≤0.26, 0≤w1≤0.25, 0≤w1≤0.24, 0≤w1≤0.23, 0≤w1≤0.22, 0≤w1≤0.21, 0≤w1≤0.2, 0≤w1≤0.15, 0≤w1≤0.1 or 0≤w1≤0.09.

[0069] For example, the lithium nickel manganese aluminum-based composite oxide of the core particle may be a cobalt-free compound that does not contain cobalt or contains a very small amount of cobalt.

[0070] The core particles may be in the form of secondary particles prepared by aggregating a plurality of primary particles. The shapes of the secondary particles may be spherical, elliptical, polyhedral, irregular or a combination thereof, and the primary particles may be spherical, elliptical, plate-shaped or a combination thereof.

[0071] When the battery is operated under high voltage or high temperature conditions, the core particles are susceptible to chemical corrosion by components in the electrolyte and may undergo many side reactions with the electrolyte. As a result, there are problems of reduced battery cycle life and safety due to the generation of a large amount of gas, but these problems can be solved by introducing a coating according to some embodiments to be described later.

[0072] coating

[0073] Based on about 100 mol% of the total metal other than lithium in the positive electrode active material, the aluminum content (e.g., amount) in the coating is about 0.1 mol% to about 2 mol%, such as about 0.2 mol% to about 1.9 mol%, about 0.3 mol% to about 1.8 mol%, about 0.5 mol% to about 1.5 mol% or about 0.8 mol% to about 1.3 mol%. The aluminum content (e.g., amount) in the coating refers only to the aluminum content (e.g., amount) included in the coating, which is separated from the aluminum contained in the core particles. The aluminum content (e.g., amount) in the coating can be measured by, for example, SEM-EDS analysis of the surface or cross section of the positive electrode active material. When the aluminum content (e.g., amount) in the coating satisfies the above range, the coating can have a substantially uniform and thin thickness, can not increase the resistance of the positive electrode active material and effectively inhibit or reduce the side reaction with the electrolyte, thereby improving the cycle life characteristics of the rechargeable lithium battery under high voltage and high temperature conditions. For example, when the aluminum content (e.g., amount) in the coating is excessive, the initial charge capacity, initial discharge capacity, initial efficiency, and cycle life characteristics may deteriorate because a substantially uniform coating is not formed or the resistance increases, but when the aluminum content (e.g., amount) in the coating is too low, because the coating may not have an appropriate or suitable thickness, the effect of suppressing side reactions with the electrolyte may deteriorate.

[0074] The coating according to some embodiments may be a film that continuously surrounds (e.g., surrounds) the surface of the core particle (e.g., in the form of a film that continuously surrounds (e.g., surrounds) the surface of the core particle), for example, it may include a shell that surrounds (e.g., surrounds) the entire surface of the core particle (e.g., in the form of a shell that surrounds (e.g., surrounds) the entire surface of the core particle). This is different from the structure in which the coating is coated on a portion of the surface of the core particle. The coating according to some embodiments may be formed to have a very thin and substantially uniform thickness and completely cover the surface of the core particle, which may neither increase the resistance of the positive electrode active material nor degrade the capacity, but rather exhibit improved structural stability, and may effectively inhibit or reduce side reactions with the electrolyte, thereby reducing the amount of gas generated under high voltage and high temperature conditions, and achieving long cycle life characteristics.

[0075] The coating may have a thickness of about 30 nanometers (nm) to about 200 nm, such as about 30 nm to about 150 nm, about 50 nm to about 200 nm, about 80 nm to about 200 nm, or about 100 nm to about 200 nm. When the thickness of the coating satisfies the above range, the structural stability of the positive electrode active material can be improved without increasing resistance or reducing capacity due to the coating, and the side reaction with the electrolyte can be effectively suppressed or reduced. The thickness of the coating can be measured by, for example, TOF-SIMS, XPS (X-ray spectroscopy) or EDS analysis, and the thickness range of the coating can be measured by a TEM-EDS line distribution diagram.

[0076] The coating according to some embodiments is characterized as having a thin and substantially uniform thickness at the level of tens of nanometers to hundreds of nanometers. For example, in one positive electrode active material particle, the thickness of the coating may have a deviation of about 20% or less, about 18% or less, or about 15% or less. In this article, the deviation of the thickness of the coating refers to the deviation of the thickness of the coating in one positive electrode active material particle. For example, the thickness of the coating can be calculated by measuring the individual thicknesses at about 10 points on the electron microscope image of the cross section of a positive electrode active material particle, calculating the arithmetic mean thereof, and then dividing the absolute value of the difference between the measured value of each thickness and the arithmetic mean by the arithmetic mean, and multiplying the quotient by 100. The deviation of the thickness of the coating is calculated. When the deviation of the thickness of the coating satisfies the above range, the coating having a substantially uniform thickness can be well formed as a film on the surface of the positive electrode active material particle, which can improve the structural stability of the positive electrode active material and effectively inhibit or reduce the side reaction with the electrolyte, resulting in minimizing or reducing the resistance increase or capacity degradation caused by the coating.

[0077] The coating may include an aluminum compound having a layered structure. In other words, the coating may include a lithium aluminum oxide such as LiAlO2 having a layered structure. The coating having a layered structure may be formed as a thin and substantially uniform film on the surface of the core particle to protect the core particle and make the movement of lithium smoother and increase the capacity, thereby improving the cycle life characteristics.

[0078] On the other hand, in addition to aluminum, the coating may further include nickel, manganese, or a combination thereof. When the nickel and / or manganese initially contained in the core particles may flow into the coating during the formation of the coating, their respective contents (e.g., amounts) are not particularly limited. The coating according to some embodiments may be referred to as an aluminum-rich coating, which must contain aluminum and optionally include nickel and / or manganese, and is also formed to have a thin and substantially uniform thickness to improve the high voltage characteristics of the positive electrode active material and enhance the cycle life characteristics.

[0079] Grain boundary coating

[0080] During the formation of the coating, aluminum may diffuse into the core particles. Accordingly, the positive electrode active material according to some embodiments may further include a grain boundary coating portion, which is disposed on the surface of the primary particles inside the secondary particles and contains aluminum. In this article, the secondary particles refer to the core particles, and the interior of the secondary particles may refer to the entire interior except the surface of the secondary particles, or to the area of ​​about 60% of the length from the surface of the secondary particles to the radius toward the center of the secondary particles. The grain boundary coating portion is different from the coating on the surface of the core particles, and refers to the coating portion formed on the surface of the primary particles inside the core particles. The presence of the grain boundary coating portion can be confirmed by SEM-EDS analysis of the cross section of the positive electrode active material, etc. In this article, the grain boundary coating portion is formed as an aluminum grain boundary coating portion, which structurally stabilizes the positive electrode active material and improves the cycle life characteristics.

[0081] The aluminum content (eg, amount) in the grain boundary coating portion is not particularly limited, but may be, for example, smaller than the aluminum content (eg, amount) in the coating layer.

[0082] Similar to the above-mentioned coating, the grain boundary coating portion may also include an aluminum compound having a layered structure. For example, the grain boundary coating portion may include a lithium aluminum oxide such as LiAlO2 having a layered structure. The grain boundary coating portion having a layered structure formed inside the core particle may promote the movement of lithium, increase capacity, and improve structural stability, thereby improving cycle life characteristics.

[0083] In addition, the grain boundary coating portion may further include nickel, manganese, or a combination thereof in addition to aluminum. The grain boundary coating portion may be referred to as an aluminum-rich coating portion.

[0084] The average particle size (D50) of the positive electrode active material according to some embodiments is not particularly limited, but may be, for example, about 10 μm to about 18 μm, about 11 μm to about 16 μm, or about 12 μm to about 15 μm. The average particle size (D50) refers to the diameter of particles with a cumulative volume of 50% by volume in a particle size distribution obtained by randomly measuring the size (diameter or major axis length) of about 20 particles in a scanning electron microscope image of the positive electrode active material. When the average particle size (D50) of the positive electrode active material satisfies the above range, high capacity and long cycle life can be achieved, and this is advantageous for the coating according to some embodiments.

[0085] In the positive electrode active material according to some embodiments, the cobalt content (e.g., amount) may be, for example, about 0.01 mol% or less, about 0.005 mol% or less, about 0.001 mol% or less, or, for example, about 0 mol% to about 0.01 mol% based on 100 mol% of the total metals other than lithium. The positive electrode active material according to some embodiments may be, for example, a positive electrode active material that does not contain cobalt.

[0086] In some embodiments, another positive electrode active material may be characterized as not containing sodium. Generally speaking, in the process of preparing the positive electrode active material, sodium ions may be used, but according to the manufacturing method described later, core particles having a stable structure and a coating layer having a substantially uniform thickness may be formed without using sodium ions.

[0087] Method for preparing positive electrode active material

[0088] In some embodiments, the method for preparing a positive electrode active material includes mixing a nickel-manganese-aluminum composite hydroxide and a lithium raw material and performing a first heat treatment to obtain a lithium-nickel-manganese-aluminum composite oxide, and adding the obtained lithium-nickel-manganese-aluminum composite oxide to a solution of an aqueous solvent of an aluminum raw material and mixing it with a solution of an aqueous solvent of an aluminum raw material, drying and performing a second heat treatment to obtain a positive electrode active material. Based on 100 mol% of the total metal other than lithium in the nickel-manganese-aluminum composite hydroxide, the nickel content (e.g., amount) is about 60 mol% to about 80 mol% and the aluminum content (e.g., amount) is about 1 mol% to about 3 mol%, and based on 100 mol% of the total metal other than lithium in the positive electrode active material, the aluminum content (e.g., amount) in the aluminum raw material is about 0.1 mol% to about 2 mol%. By this method, the aforementioned positive electrode active material can be manufactured.

[0089] The nickel-manganese-aluminum composite hydroxide is a precursor of the core particles, and the precursor of the core particles includes secondary particles in which a plurality of primary particles are aggregated and may not include cobalt or include a very small amount of cobalt (for example, in the form of secondary particles in which a plurality of primary particles are aggregated and may not include cobalt or include a very small amount of cobalt), and the precursor of the core particles may be, for example, a nickel-manganese-aluminum composite hydroxide that does not contain cobalt. The nickel-manganese-aluminum composite hydroxide can be manufactured by a common coprecipitation method.

[0090] The method for preparing a positive electrode active material according to some embodiments is characterized by using a precursor of a nickel-manganese-aluminum composite hydroxide when manufacturing core particles without additionally doping aluminum, wherein aluminum is uniformly dispersed in the structure by preparing the precursor using an aluminum-containing compound. Such a precursor can be used to realize a positive electrode active material that can stably maintain a layered structure without the presence of cobalt despite repeated charging and discharging, and because no aluminum byproduct or aluminum aggregate is formed, the initial charge capacity, initial discharge capacity, initial efficiency characteristics, and cycle life characteristics of the positive electrode active material can be improved.

[0091] Based on 100mol% of total metal in nickel-manganese-aluminum composite hydroxide, nickel content (e.g., amount) can be about 60mol% to about 80mol%, such as about 65mol% to about 80mol%, about 70mol% to about 80mol%, about 60mol% to about 79mol%, about 60mol% to about 78mol% or about 60mol% to about 75mol%. When nickel content (e.g., amount) meets the above range, high capacity can be achieved, and even if cobalt content (e.g., amount) is reduced, structural stability can also be increased. This nickel-manganese-aluminum composite hydroxide is different from a high nickel composite hydroxide having a nickel content (e.g., amount) greater than about 80mol%. Because the nickel-manganese-aluminum composite hydroxide according to some embodiments has different surface features from the high nickel composite hydroxide, such as different residual lithium content (e.g., amount), pH, shape, etc. on the surface, the same coating method may not be applicable.

[0092] Based on about 100 mol% of the total metal in the nickel-manganese-aluminum composite hydroxide, the manganese content (e.g., amount) in the nickel-manganese-aluminum composite hydroxide may be about 10 mol% to about 39 mol%, such as about 10 mol% to about 35 mol%, about 10 mol% to about 30 mol%, about 10 mol% to about 29 mol%, about 15 mol% to about 39 mol%, about 20 mol% to about 39 mol%, or about 20 mol% to about 30 mol%. In some embodiments, based on about 100 mol% of the total metal in the nickel-manganese-aluminum composite hydroxide, the aluminum content (e.g., amount) in the nickel-manganese-aluminum composite hydroxide may be about 1 mol% to about 3 mol%, such as about 1 mol% to about 2.5 mol%, about 1 mol% to about 2 mol%, or about 1 mol% to about 1.9 mol%. When the manganese and aluminum contents of the nickel-manganese-aluminum composite hydroxide meet the above ranges, high capacity can be achieved, while the structural stability of the positive electrode active material can be increased, and the production cost can be reduced to increase economic efficiency.

[0093] In the nickel-manganese-aluminum composite hydroxide, the cobalt content (e.g., amount) may be less than or equal to about 0.01 mol%, less than or equal to about 0.005 mol%, or less than or equal to about 0.001 mol%, based on 100 mol% of the total metal in the nickel-manganese-aluminum composite hydroxide. The nickel-manganese-aluminum composite hydroxide is economical because it avoids the increase in unit cost caused by cobalt, maximizes or increases capacity, and improves structural stability.

[0094] The nickel-manganese-aluminum composite hydroxide can be represented by Chemical Formula 2.

[0095] Chemical formula 2

[0096] Ni x2 Mn y2 Alz2 M 2 w2 (OH)2,

[0097] In Chemical Formula 2, 0.6≤x2≤0.8, 0.1≤y2≤0.39, 0.01<z2≤0.03, 0≤w2≤0.29, and 0.9≤x2+y2+z2+w2≤1.1, and M 2 It is one or more elements selected from B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W and Zr.

[0098] The nickel-manganese-aluminum-based composite hydroxide is in the form of particles, and the particles have an average particle size (D50) of about 10 μm to about 18 μm, about 11 μm to about 16 μm, or about 12 μm to about 15 μm.

[0099] The nickel-manganese-aluminum composite hydroxide and the lithium raw material may be mixed in a molar ratio of about 1:0.9 to about 1:1.8, for example, about 1:0.9 to about 1:1.5 or about 1:0.9 to about 1:1.2.

[0100] The first heat treatment may be performed in an oxygen atmosphere at a temperature range of, for example, about 750° C. to about 950° C., about 780° C. to about 900° C., or about 810° C. to about 890° C. for about 2 hours to about 20 hours or about 4 hours to about 12 hours.

[0101] By the first heat treatment, a lithium nickel manganese aluminum composite oxide can be obtained. Based on the total metal other than about 100 mol% of lithium in the obtained lithium nickel manganese aluminum composite oxide, the obtained lithium nickel manganese aluminum composite oxide may include about 60 mol% or more, for example, about 60 mol% to about 80 mol% of nickel, but does not include cobalt or includes a very small amount of cobalt of about 0.01 mol%. Because this lithium nickel manganese aluminum composite oxide has a significantly different residual lithium content (e.g., amount) and different surface characteristics from oxides having other compositions (e.g., nickel oxides such as lithium nickel cobalt manganese composite oxides or lithium nickel cobalt aluminum composite oxides, etc.), the coating method may not be able to successfully form a good or appropriate coating thereon in the form of a substantially uniform film. However, some embodiments propose a method for improving high voltage and high temperature characteristics by forming a very thin and substantially uniform thickness coating on the surface of a lithium nickel manganese aluminum composite oxide having a nickel content (e.g., amount) of about 60 mol% to about 80 mol% and a very small cobalt content (e.g., amount).

[0102] In some embodiments, the lithium nickel manganese aluminum composite oxide obtained by the first heat treatment is added to an aqueous solvent mixed with an aluminum raw material, and then mixed, and then dried and subjected to a second heat treatment to form a coating according to some embodiments. This is a type or kind of wet coating method.

[0103] The aqueous solvent may include distilled water, an alcohol solvent, or a combination thereof.

[0104] The aluminum raw material may include, for example, aluminum nitrate, aluminum sulfate, aluminum carbonate, aluminum hydroxide, or a combination thereof. For example, the aluminum raw material may include aluminum sulfate, which is conducive to forming a coating having a substantially uniform thickness on the surface of the lithium nickel manganese aluminum composite oxide particles.

[0105] The aluminum raw material is a raw material for forming a coating and can be designed to have an aluminum content (e.g., amount) ranging from about 0.1 mol% to about 2 mol%, such as about 0.2 mol% to about 1.9 mol%, about 0.3 mol% to about 1.8 mol%, about 0.5 mol% to about 1.5 mol% or about 0.8 mol% to about 1.3 mol%, based on the total metal other than 100 mol% of lithium in the positive electrode active material finally obtained. When the content of the raw material of the coating is designed to have the above range, the coating can be formed to have a thin and substantially uniform thickness of tens to hundreds of nanometers, which can reduce the amount of gas generated by the rechargeable lithium battery under high voltage or high temperature conditions, and achieve high capacity and long cycle life characteristics.

[0106] The solution prepared by mixing the aluminum raw material with an aqueous solvent may have a pH of about 1.5 to about 3.5, for example, about 2.0 to about 3.4, about 2.5 to about 3.3, about 2.7 to about 3.3, or about 2.9 to about 3.2. The lithium nickel manganese aluminum composite oxide is added to the solution of the aqueous solvent of the aluminum raw material and mixed with the solution of the aqueous solvent of the aluminum raw material for about 5 minutes to about 80 minutes, about 5 minutes to about 60 minutes, or about 5 minutes to about 40 minutes. After stirring, the mixed solution may have a pH of about 4.5 to about 8.5, for example, about 5.0 to about 8.0, about 5.5 to about 7.5, or about 6.0 to about 7.0. When these conditions are met, it is beneficial to form a coating having a substantially uniform thickness (e.g., the formation of a coating having a substantially uniform thickness is enhanced).

[0107] After mixing, drying is performed at, for example, about 40° C. to about 240° C., about 100° C. to about 220° C., or about 150° C. to about 200° C. to remove the aqueous solvent.

[0108] The second heat treatment can be understood as forming a coating and, for example, about 700°C to about 850°C, about 750°C to about 840°C, or about 800°C to about 830°C in an oxygen atmosphere for about 2 hours to about 20 hours or about 3 hours to about 10 hours. In some embodiments, the temperature of the second heat treatment may be lower than the temperature of the first heat treatment, and the time of the second heat treatment may be equal to or less than the time of the first heat treatment. Under these conditions, a second heat treatment may be performed to obtain a desired or appropriate coating.

[0109] Positive electrode

[0110] In some embodiments, the positive electrode includes a positive electrode current collector and a positive electrode active material layer on the positive electrode current collector, wherein the positive electrode active material layer includes the aforementioned positive electrode active material. In addition to the aforementioned positive electrode active material, the positive electrode active material layer may further include other types (kinds) of positive electrode active materials. In addition, the positive electrode active material layer may optionally further include a binder, a conductive material, or a combination thereof.

[0111] According to some embodiments, the loading level of the positive electrode active material layer may be about 10 mg / cm 2 ~ about 40mg / cm 2 , for example about 10 mg / cm 2 ~about 30mg / cm 2 or about 10 mg / cm 2 ~about 20mg / cm 2 . In addition, the density of the positive electrode active material layer in the final pressed positive electrode may be about 3.3 g / cc to about 3.7 g / cc, for example, about 3.3 g / cc to about 3.6 g / cc or about 3.4 g / cc to about 3.58 g / cc. When the positive electrode active material according to some embodiments is applied, it is advantageous to implement such a load level and density of the positive electrode active material layer, and the positive electrode satisfying the load level and density of the positive electrode active material layer within the above range is suitable for implementing a high-capacity, high-energy-density rechargeable lithium battery.

[0112] Binder

[0113] The binder improves the bonding properties of the positive electrode active material particles to each other and the bonding properties of the positive electrode active material particles to the positive electrode current collector. Examples of the binder may include polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, (meth) acrylated styrene-butadiene rubber, epoxy resin, (meth) acrylic resin, polyester resin and nylon, but are not limited thereto.

[0114] Conductive Materials

[0115] A conductive material (e.g., a conductor, an electronic conductor, an electrical conductor, etc.) is included to provide electrode conductivity, and any conductive material can be used as the conductive material unless it causes a chemical change. Examples of the conductive material may include carbon-based materials (such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanofiber, and carbon nanotube); metal-based materials containing copper, nickel, aluminum, silver, etc. and including metal powder or metal fiber (e.g., in the form of metal powder or metal fiber); conductive polymers (such as polyphenylene derivatives); or mixtures thereof.

[0116] The content (eg, amount) of the binder and the conductive material may be about 0.5 wt % to about 5 wt %, respectively, based on about 100 wt % of the positive electrode active material layer.

[0117] The positive electrode current collector may include Al foil, but is not limited thereto.

[0118] Rechargeable lithium battery

[0119] Some embodiments provide a rechargeable lithium battery including the aforementioned positive electrode, a negative electrode, and an electrolyte.

[0120] Depending on the shape, the rechargeable lithium batteries may be classified into a cylindrical shape, a prismatic shape, a pouch shape, a coin shape, etc. Figure 1 FIG2 is a perspective view schematically showing a rechargeable lithium battery according to some embodiments. Figure 1 , the rechargeable lithium battery 100 includes an electrode assembly 40 having a separator 30 interposed between a positive electrode 10 and a negative electrode 20, and a case 50 accommodating the electrode assembly 40 therein. The positive electrode 10, the negative electrode 20, and the separator 30 may be impregnated with an electrolyte.

[0121] The rechargeable lithium battery according to some embodiments may be charged at a high voltage, or may be suitable for driving at a high voltage. For example, the charging voltage of the rechargeable lithium battery may be greater than or equal to about 4.45V, about 4.45V to about 4.7V, about 4.45V to about 4.6V, or about 4.45V to about 4.55V. By applying the positive electrode active material according to some embodiments, the rechargeable lithium battery can significantly reduce the amount of gas generated even when charged at a high voltage, and can achieve high capacity and long cycle life characteristics.

[0122] Negative electrode

[0123] The negative electrode may include a negative electrode current collector and a negative electrode active material layer on the negative electrode current collector, and may further include a negative electrode active material, a binder, a conductive material, or a combination thereof.

[0124] Negative electrode active material

[0125] The negative electrode active material may include a material that reversibly intercalates / deintercalates lithium ions, lithium metal, a lithium metal alloy, a material capable of doping / dedoping lithium, or a transition metal oxide.

[0126] The material that reversibly intercalates / deintercalates lithium ions may include, for example, crystalline carbon, amorphous carbon, or a combination thereof as a carbonaceous negative electrode active material. The crystalline carbon may be amorphous natural graphite or artificial graphite, or may be natural graphite or artificial graphite in the form of flakes, sheets, spheres, or fibers. The amorphous carbon may be soft carbon, hard carbon, a mesophase pitch carbonization product, calcined coke, etc.

[0127] Lithium metal alloys include alloys of lithium and a metal selected from the group consisting of Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn.

[0128] The material capable of doping / dedoping lithium may be a Si-based negative electrode active material or a Sn-based negative electrode active material. The Si-based negative electrode active material may include silicon, silicon-carbon composites, SiO x (0<x≤2), Si-Q alloy (wherein Q is an element selected from alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements (excluding Si), Group 15 elements, Group 16 elements, transition metals, rare earth elements and combinations thereof, such as Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po and combinations thereof) or combinations thereof. The Sn-based negative electrode active material may be Sn, SnO2, a Sn alloy or a combination thereof.

[0129] The silicon-carbon composite may be a composite of silicon and amorphous carbon. The average particle size (D50) of the silicon-carbon composite particles may be, for example, about 0.5 μm to about 20 μm. According to some embodiments, the silicon-carbon composite may include silicon particles and amorphous carbon coated on the surface of the silicon particles (for example, in the form of silicon particles and amorphous carbon coated on the surface of the silicon particles). For example, the silicon-carbon composite may include secondary particles (cores) in which silicon primary particles are assembled and an amorphous carbon coating (shell) on the surface of the secondary particles. Amorphous carbon may also be present between silicon primary particles, for example, silicon primary particles may be coated with amorphous carbon. Secondary particles may be dispersed in an amorphous carbon matrix.

[0130] The silicon-carbon composite may further include crystalline carbon. For example, the silicon-carbon composite may include: a core including crystalline carbon and silicon particles and an amorphous carbon coating on the surface of the core. The crystalline carbon may be artificial graphite, natural graphite, or a combination thereof. The amorphous carbon may include soft carbon, hard carbon, mesophase pitch carbonization product, and calcined coke.

[0131] When the silicon-carbon composite includes silicon and amorphous carbon, the content (e.g., amount) of silicon may be about 10 wt% to about 50 wt% and the content (e.g., amount) of amorphous carbon may be about 50 wt% to about 90 wt% based on about 100 wt% of the silicon-carbon composite. In some embodiments, when the silicon-carbon composite includes silicon, amorphous carbon, and crystalline carbon, the content (e.g., amount) of silicon may be about 10 wt% to about 50 wt%, the content (e.g., amount) of crystalline carbon may be about 10 wt% to about 70 wt%, and the content (e.g., amount) of amorphous carbon may be about 20 wt% to about 40 wt% based on about 100 wt% of the silicon-carbon composite.

[0132] In addition, the thickness of the amorphous carbon coating may be about 5 nm to about 100 nm. The average particle size (D50) of the silicon particles (primary particles) may be about 10 micrometers (μm) to about 1 nm or about 10 nm to about 200 nm. The silicon particles may exist as silicon alone, in the form of a silicon alloy, or in an oxidized form of silicon. The oxidized form of silicon may be SiO x (0<x≤2) represents. At this time, the atomic content (e.g., amount) ratio of Si:O indicating the degree of oxidation may be about 99:1 to about 33:67. As utilized herein, when no definition is otherwise provided, the average particle size (D50) indicates the diameter of particles in which the cumulative volume in the particle distribution is about 50 volume %.

[0133] The Si-based negative electrode active material or the Sn-based negative electrode active material may be mixed with the carbon-based negative electrode active material. When the Si-based negative electrode active material or the Sn-based negative electrode active material and the carbon-based negative electrode active material are mixed and used, the mixing ratio may be about 1:99 to about 90:10 by weight.

[0134] Binder

[0135] The binder is used to bind the negative electrode active material particles well to each other and also to bind the negative electrode active material to the negative electrode current collector. The binder may be a non-aqueous binder, an aqueous binder, a dry binder or a combination thereof.

[0136] The non-aqueous binder may include polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene propylene copolymer, polystyrene, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamideimide, polyimide, or a combination thereof.

[0137] The aqueous binder may include styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, (meth)acrylonitrile-butadiene rubber, (meth)acrylic rubber, butyl rubber, fluororubber, polyethylene oxide, polyvinyl pyrrolidone, polyepichlorohydrin, polyphosphazene, poly(meth)acrylonitrile, ethylene propylene diene copolymer, polyvinyl pyridine, chlorosulfonated polyethylene, latex, polyester resin, (meth)acrylic resin, phenol resin, epoxy resin, polyvinyl alcohol or a combination thereof.

[0138] When the aqueous binder is used as a binder in the negative electrode active material layer, it may further contain a cellulose compound capable of imparting viscosity. The cellulose compound may be one or more types (species) of carboxymethyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose and alkali metal salts thereof. The alkali metal may be Na, K or Li.

[0139] The dry binder may be a polymer material that can be turned into fibers, and may be, for example, polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, or a combination thereof.

[0140] Conductive Materials

[0141] A conductive material (e.g., conductor) is included to provide electrode conductivity and any conductive material can be used as the conductive material unless it causes a chemical change. Specific examples of the conductive material may include carbon-based materials (such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanofiber, and carbon nanotube); metal-based materials in the form of metal powder or metal fiber including copper, nickel, aluminum, silver, etc.; conductive polymers (such as polyphenylene derivatives); or mixtures thereof.

[0142] Based on about 100wt% of the negative electrode active material layer, the content (e.g., amount) of the negative electrode active material may be about 95wt% to about 99.5wt%, and based on about 100wt% of the negative electrode active material layer, the content (e.g., amount) of the binder may be about 0.5wt% to about 5wt%. For example, the negative electrode active material layer may include about 90wt% to about 99wt% of the negative electrode active material, about 0.5wt% to about 5wt% of the binder, and about 0.5wt% to about 5wt% of the conductive material.

[0143] current collector

[0144] The negative electrode current collector may include, for example, indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li) or an alloy thereof, and may include foil, sheet or foam (e.g., in the form of foil, sheet or foam). The thickness of the negative electrode current collector may be, for example, about 1 μm to about 20 μm, about 5 μm to about 15 μm, or about 7 μm to about 10 μm.

[0145] Electrolyte

[0146] For example, the electrolyte for a rechargeable lithium battery may be an electrolyte that may include a non-aqueous organic solvent and a lithium salt.

[0147] The non-aqueous organic solvent is used as a medium for transporting ions participating in the electrochemical reaction of the battery. The non-aqueous organic solvent may be a carbonate solvent, an ester solvent, an ether solvent, a ketone solvent, an alcohol solvent, an aprotic solvent, or a combination thereof.

[0148] Carbonate solvents may include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), ethyl methyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), etc. Ester solvents may include methyl acetate, ethyl acetate, n-propyl acetate, dimethyl acetate, methyl propionate, ethyl propionate, decanoic acid lactone, mevalonolactone, valerolactone, caprolactone, etc.

[0149] Ether solvents may include dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, dimethoxyethane, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, tetrahydrofuran, etc. In some embodiments, ketone solvents may include cyclohexanone, etc. Alcohol solvents may include ethanol, isopropanol, etc., and aprotic solvents may include nitriles (such as R-CN, where R is a C2-C20 straight chain hydrocarbon group, a branched hydrocarbon group, or a cyclic hydrocarbon group, and may include a double bond, an aromatic ring, or an ether bond, etc.); amides (such as dimethylformamide); dioxolanes (such as 1,3-dioxolanes, 1,4-dioxolanes, etc.); sulfolane, etc.

[0150] A single non-aqueous organic solvent may be used or two or more types (kinds) of non-aqueous organic solvents may be used as a mixture, and when two or more types (kinds) of non-aqueous organic solvents are used as a mixture, the mixing ratio may be appropriately adjusted according to the desired or appropriate battery performance, which is well known to those skilled in the art.

[0151] In some embodiments, when a carbonate-based solvent is used, a cyclic carbonate and a chain carbonate may be mixed and used, and the cyclic carbonate and the chain carbonate may be mixed in a volume ratio of about 1:1 to about 1:9.

[0152] The non-aqueous organic solvent may further include an aromatic hydrocarbon organic solvent. For example, the carbonate-based solvent and the aromatic hydrocarbon organic solvent may be mixed and utilized in a volume ratio of about 1:1 to about 30:1.

[0153] The electrolyte may further include vinyl ethyl carbonate, vinylene carbonate or ethylene carbonate compounds to improve the battery cycle life.

[0154] Examples of the ethylene carbonate-based compound may include fluoroethylene carbonate, difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, and cyanoethylene carbonate.

[0155] The lithium salt dissolved in the non-aqueous organic solvent supplies lithium ions in the battery, ensures the basic operation of the rechargeable lithium battery, and improves the transport of lithium ions between the positive electrode and the negative electrode. Examples of lithium salts include those selected from LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, LiCl, LiI, LiN(SO3C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide; LiFSI), LiC4F9SO3, LiN(C x F 2x+1 SO2)(C y F 2y+1 SO2) (wherein x and y are integers of 1 to 20), at least one of lithium trifluoromethanesulfonate, lithium tetrafluoroethanemethanesulfonate, lithium difluorobis(oxalato)phosphate (LiDFOB) and lithium bis(oxalato)borate (LiBOB).

[0156] The concentration of the lithium salt may be in the range of about 0.1 M to about 2.0 M. When the concentration of the lithium salt is within the above range, the electrolyte has appropriate or suitable ion conductivity and viscosity, and thus excellent or appropriate performance may be achieved, and lithium ions may be efficiently moved.

[0157] Diaphragm

[0158] Depending on the type or kind of rechargeable lithium battery, the separator may be present between the positive electrode and the negative electrode. The separator may include a polyethylene separator, a polypropylene separator, a polyvinylidene fluoride separator, or a multilayer film of two or more layers thereof (such as a polyethylene / polypropylene two-layer separator, a polyethylene / polypropylene / polyethylene three-layer separator, a polypropylene / polyethylene / polypropylene three-layer separator, etc.).

[0159] The separator may include a porous substrate and a coating layer including an organic material, an inorganic material, or a combination thereof on one or both surfaces (eg, opposing surfaces) of the porous substrate.

[0160] The porous substrate can be a polymer film formed from any polymer polyolefin (such as polyethylene and polypropylene), polyester (such as polyethylene terephthalate and polybutylene terephthalate), polyacetal, polyamide, polyimide, polycarbonate, polyether ketone, polyaryletherketone, polyetherimide, polyamideimide, polybenzimidazole, polyethersulfone, polyoxyxylene, cyclic olefin copolymer, polyphenylene sulfide, polyethylene naphthalate, glass fiber and polytetrafluoroethylene, or a copolymer or mixture of two or more thereof.

[0161] The porous substrate may have a thickness of about 1 μm to about 40 μm, for example, about 1 μm to about 30 μm, about 1 μm to about 20 μm, about 5 μm to about 15 μm, or about 10 μm to about 15 μm.

[0162] The organic material may include a (meth)acryl-based copolymer including a first structural unit (derived from (meth)acrylamide) and a second structural unit (including at least one of a structural unit derived from (meth)acrylic acid or (meth)acrylate and a structural unit derived from (meth)acrylamide sulfonic acid or a salt thereof).

[0163] The inorganic material may include inorganic particles selected from Al2O3, SiO2, TiO2, SnO2, CeO2, MgO, NiO, CaO, GaO, ZnO, ZrO2, Y2O3, SrTiO3, BaTiO3, Mg(OH)2, boehmite, and combinations thereof, but is not limited thereto. The average particle size (D50) of the inorganic particles may be from about 1 nm to about 2000 nm, for example, from about 100 nm to about 1000 nm or from about 100 nm to about 700 nm.

[0164] An organic material and an inorganic material may be mixed in one coating layer, or a coating layer including an organic material and a coating layer including an inorganic material may be stacked.

[0165] The coating layer may have a thickness of about 0.5 μm to about 20 μm, for example, about 1 μm to about 10 μm or about 1 μm to about 5 μm.

[0166] The following describes examples and comparative examples of the present disclosure. However, the following examples are merely examples of the present disclosure, and the present disclosure is not limited to the following examples.

[0167] Example 1

[0168] 1. Manufacturing positive electrode active material

[0169] Ni 0.75 Mn 0.23 Al 0.02(OH)2 and LiOH are mixed in a molar ratio of about 1:1 and then subjected to a first heat treatment at about 850°C for about 8 hours in an oxygen atmosphere to produce a LiNi 0.75 Mn 0.23 Al 0.02 O2 and a composite oxide in the form of secondary particles having an average particle size (D50) of about 14 μm.

[0170] After mixing aluminum sulfate in a distilled water solvent, add the composite oxide produced thereto, then, mix for about 20 minutes to about 60 minutes. In this article, based on the total metal other than about 100wt% of lithium in the final positive electrode active material, the aluminum content (e.g., amount) of aluminum sulfate is designed to be about 1.0mol%. After removing the solvent from the mixed solution, the residue is dried at about 190°C and a second heat treatment is performed at about 825°C in an oxygen atmosphere for about 8 hours to obtain the final positive electrode active material.

[0171] 2. Manufacturing of rechargeable lithium battery cells

[0172] About 98.5 wt % of the positive electrode active material, about 1.0 wt % of the polyvinylidene fluoride binder and about 0.5 wt % of the carbon nanotube conductive material are mixed to prepare a positive electrode active material layer slurry, and the slurry is coated on an aluminum foil current collector, and then dried and pressed to manufacture a positive electrode. In this paper, the positive electrode is prepared at 10 mg / cm 2 The positive electrode active material layer was formed at a loading level of , and the final pressed positive electrode active material layer had a density of about 3.4 g / cc.

[0173] On the other hand, a negative electrode active material layer slurry is prepared by mixing about 97.5wt% of a graphite negative electrode active material, about 1.5wt% of a carboxymethyl cellulose and about 1wt% of a styrene butadiene rubber in an aqueous solvent. The negative electrode active material layer slurry is coated on a copper foil current collector, and then dried and pressed to manufacture a negative electrode.

[0174] A rechargeable lithium battery cell was manufactured in a conventional method using a polytetrafluoroethylene separator and using an electrolyte prepared by dissolving about 1 M LiPF6 in a mixed solvent of ethylene carbonate and dimethyl carbonate in a volume ratio of about 3:7.

[0175] Example 2

[0176] A positive electrode active material and a rechargeable lithium battery cell were manufactured in substantially the same manner as in Example 1, except that the aluminum content (eg, amount) in aluminum sulfate was designed to be about 0.5 mol % based on about 100 wt % of total metals other than lithium in the final positive electrode active material.

[0177] Example 3

[0178] A positive electrode active material and a rechargeable lithium battery cell were manufactured in substantially the same manner as in Example 1, except that the aluminum content (eg, amount) in aluminum sulfate was designed to be about 1.5 mol % based on about 100 wt % of total metals other than lithium in the final positive electrode active material.

[0179] Example 4

[0180] A positive electrode active material and a rechargeable lithium battery cell were manufactured in substantially the same manner as in Example 1, except that the aluminum content (eg, amount) in aluminum sulfate was designed to be about 2.0 mol % based on about 100 wt % of total metals other than lithium in the final positive electrode active material.

[0181] Comparative Example 1

[0182] Ni 0.75 Mn 0.25 (OH)2, LiOH and Al2O3 were mixed in a molar ratio of about 1:1:0.02 and then heat-treated at about 850°C for about 8 hours in an oxygen atmosphere to prepare a LiNi 0.75 Mn 0.23 Al 0.02 O2 and an aluminum-doped composite oxide in the form of secondary particles having an average particle size (D50) of about 14 μm. This was used as a positive electrode active material to manufacture a rechargeable lithium battery cell in substantially the same manner as in Example 1.

[0183] Comparative Example 2

[0184] Ni 0.75 Mn 0.23 Al 0.02 (OH)2 and LiOH were mixed in a molar ratio of about 1:1, and then, heat-treated at about 850°C for about 8 hours under an oxygen atmosphere to prepare a LiNi 0.75 Mn 0.23 Al 0.02 A composite oxide in the form of secondary particles having a composition of 1000 μm and an average particle size (D50) of about 14 μm was prepared as a positive electrode active material in substantially the same manner as in Example 1 to manufacture a rechargeable lithium battery cell.

[0185] Comparative Example 3

[0186] The positive electrode active material was prepared in substantially the same manner as in Example 1, except that the aluminum coating was performed in a dry manner. 0.75 Mn 0.23 Al 0.02 O2 composition of the secondary particles (for example, with LiNi 0.75 Mn0.23 Al 0.02 A composite oxide in the form of secondary particles of a composition of 200 Å (in the form of secondary particles of 200 Å) was mixed with alumina powder and then heat treated at about 825° C. for about 8 hours under an oxygen atmosphere to prepare an Al-coated positive electrode active material in a dry manner. This was used as a positive electrode active material to manufacture a rechargeable lithium battery cell in substantially the same manner as in Example 1.

[0187] Comparative Example 4

[0188] A rechargeable lithium battery cell was manufactured in substantially the same manner as in Example 1, except that the LiNi 0.94 Co 0.03 Al 0.03 A composite oxide in the form of secondary particles having a composition of 200 Å and an average particle size (D50) of about 14 μm was used as a positive electrode active material without forming a coating layer.

[0189] Comparative Example 5

[0190] A positive electrode active material was prepared in substantially the same manner as in Comparative Example 4, except that Al wet coating was performed in the same manner as in Example 1. This was used as a positive electrode active material to manufacture a rechargeable lithium battery cell in substantially the same manner as in Example 1.

[0191] Comparative Example 6

[0192] A positive electrode active material and a rechargeable lithium battery cell were manufactured in substantially the same manner as in Example 1, except that the aluminum content (eg, amount) of aluminum sulfate was designed to be about 3.0 mol % based on about 100 wt % of total metals other than lithium in the final positive electrode active material.

[0193] The design details of the positive electrode active materials of Examples 1 to 4 and Comparative Examples 1 to 6 are briefly provided in Table 1.

[0194] Evaluation Example 1: Comparison of Comparative Example 1 and Comparative Example 2

[0195] Figure 2 The SEM image of the positive electrode active material of Comparative Example 1 is shown, and Figure 3 1 shows a SEM image of the positive electrode active material of Comparative Example 2. The lithium nickel manganese aluminum oxide of Comparative Example 1 was prepared by synthesizing lithium nickel manganese oxide and further doping aluminum thereon, and the reference Figure 2 , confirming that the positive electrode active material has an uneven secondary particle surface, and as shown in the circled area, aluminum byproducts are formed. In contrast, in the lithium nickel manganese aluminum oxide of Comparative Example 2, in which nickel manganese aluminum hydroxide is used as a precursor, aluminum is uniformly distributed on the secondary particles at a substantially uniform concentration, and the reference Figure 3, a positive electrode active material having secondary particles with a very uniform spherical surface without aluminum by-products was successfully synthesized. The examples are understood to utilize Comparative Example 2 as a base material.

[0196] Evaluation Example 2: Comparison of coatings

[0197] Figures 4 to 9 SEM-EDS images of cross sections of the positive electrode active materials of Examples 1 to 4 and Comparative Examples 3 and 5 are shown in order. Figures 4 to 9 In addition, aluminum is highlighted. Fig.10 A SEM image of the surface of the positive electrode active material of Comparative Example 5 is shown.

[0198] like Figures 4 to 7 As shown in FIG. 1 , in the positive electrode active materials of Examples 1 to 4, a very thin aluminum coating layer having a substantially uniform thickness was successfully formed on the surface of the secondary particles to form a core-shell structure type or kind. In contrast, Figure 8 In Comparative Example 3 where a dry coating is applied, aluminum is irregularly aggregated on the surface of the secondary particles, but no coating is formed to wrap the secondary particles. Fig. 9 and Fig.10 In Comparative Example 5, which used nickel cobalt aluminum oxide having a nickel content (e.g., amount) of about 94 mol% as a base material and applied the same coating method as in Examples 1 to 4, aluminum was aggregated on the surface of the secondary particles, and a coating layer that wrapped the secondary particles was not formed. Since the positive electrode active material of Comparative Example 5 had a different composition on the surface of the composite oxide from the positive electrode active material of the Examples and a different residual lithium content (e.g., amount) and pH conditions, etc., even if the same coating method as in the Examples was applied, a substantially uniform coating layer was not formed.

[0199] Evaluation Example 3: Analysis of the coating and grain boundary coating portion of the embodiment

[0200] Fig.11 is a TOF-SIMS depth profile of the positive electrode active material of Example 1, which is a graph showing the change in the ratio of the aluminum content (eg, amount) to the nickel content (eg, amount) from the surface of the secondary particle to the inside of the secondary particle.

[0201] Fig.12 is a TEM image of a cross section of the positive electrode active material of Example 1, and Fig.13 for Fig.12 Magnified TEM image of the portion indicated by the rectangle. Fig.14 To pass Fig.13 An image obtained by EDS analysis of a TEM image, highlighting oxygen, aluminum, manganese and nickel from the left. Fig.15 To show the contents of oxygen, aluminum, manganese and nickel in Fig.13 and Fig.14 The changes in the direction of the arrows are shown in the EDS line profile.

[0202] refer to Figure 11 to Figure 15 , in the positive electrode active material of Example 1, a thin and substantially uniform Al coating layer having a thickness of about 30 nm to about 200 nm is formed on the surface of the core particle.

[0203] Fig.16 The leftmost image in FIG. 1 is a TEM image of a cross section of the positive electrode active material of Example 1, which is an enlarged view of the primary particles located at the outermost layer of the secondary particles. Fig.16 The four images on the middle right are TEM-EDS images highlighting O, Al, Mn, and Ni from left to right. Fig.17 To show the contents of O, Al, Mn and Ni Fig.16 The arrows in the figure show the changes in the direction of the EDS line profile. Fig.16 and Fig.17 , Al is coated on the interface of the primary particles located at the outermost of the secondary particles, that is, a grain boundary coating portion is formed.

[0204] Fig.18 is a TEM image of a cross section of the positive electrode active material of Example 1, and Fig.19 for Fig.18 A magnified image of area 1 (left) and an image highlighting aluminum by EDS analysis (right). Fig. 20 for Fig.18 A magnified image of region 2 (left) and an image highlighting aluminum by EDS analysis (right), and Fig.21 for Fig.18 A magnified image of area 3 (left) and an image highlighting aluminum by EDS analysis (right). Fig.18 In FIG. 1 , region 1, region 2, and region 3 sequentially show the core particles from the inside to the surface. Figure 18 to Figure 21 , at any position including the inside of the core particle, an Al grain boundary coating portion on the interface of the primary particle is formed.

[0205] Fig. 22 It is a TEM-EDS image showing an enlarged analysis of the primary particles in the outermost layer of the secondary particles in the cross section of the positive electrode active material of Example 1, and the protruding parts represent aluminum. Fig.23 Shown by Fig. 22 TEM analysis images of the parts indicated by arrows ① to ⑥. Fig.23In the figure, arrows ① to ④ indicate the surface of the secondary particles, which confirm the aluminum coating, arrow ⑤ indicates the inside of the primary particles, and arrow ⑥ indicates between the primary particles, that is, the grain boundaries, which can confirm the aluminum grain boundary coating part. Fig.23 , a layered structure was observed at all locations, such as the surface of the secondary particles, the inside of the primary particles, and the grain boundaries, etc. In other words, both the coating layer and the grain boundary coating portion (e.g., the coating layer and the grain boundary coating portion at the same time) had a layered structure, and accordingly, it was confirmed that a layered lithium aluminum oxide such as LiAlO2 was included.

[0206] Evaluation Example 4: Evaluation of electrochemical characteristics

[0207] At about 25°C, the rechargeable lithium battery cells of Examples 1 to 4 and Comparative Examples 1 to 6 were charged to an upper voltage limit of about 4.45V at a constant current of about 0.2C, and charged to about 0.05C at a constant voltage, and then discharged to a cut-off voltage of about 3.0V at about 0.2C. In Table 1, the initial charge capacity, the initial discharge capacity, and the ratio of the initial discharge capacity to the initial charge capacity as the initial efficiency are provided. Subsequently, at about 45°C, the rechargeable lithium battery cells were charged and discharged 25 times or more at about 1.0C in a voltage range of about 3.0V to about 4.45V, and the ratio of the discharge capacity of the 25th cycle to the initial discharge capacity was calculated and then provided in Table 1 as a high temperature cycle life.

[0208] Table 1

[0209]

[0210] Comparative Example 1 is compared with Comparative Example 2 (i.e., when compared with Comparative Example 1 in which aluminum is additionally doped), Comparative Example 2 in which aluminum is introduced into the precursor exhibits increased initial charge capacity / initial discharge capacity and improved high temperature cycle life characteristics. In the example using Comparative Example 2 as a base material and forming a substantially uniform coating using a specific method according to some embodiments, by coating Al in a content (e.g., amount) of about 2 mol% or less, improved initial charge capacity / initial discharge capacity and initial efficiency and high temperature cycle life characteristics are simultaneously (e.g., simultaneously) exhibited.

[0211] In Comparative Example 3 in which a dry coating type or kind was applied, since a substantially uniform coating was not formed as in Evaluation Example 2, high temperature cycle life characteristics were significantly deteriorated compared to Examples 1 to 4.

[0212] Compared to Examples 1 to 4, Comparative Examples 4 and 5, each of which utilizes lithium nickel cobalt aluminum oxide having a nickel content (e.g., amount) of about 94 mol%, exhibit high initial charge capacity / initial discharge capacity and initial efficiency, but high temperature cycle life characteristics deteriorate, and there is a problem of increased cost due to the use of cobalt. In Comparative Example 5, in which the same coating method as in Examples 1 to 4 is applied to the base material of Comparative Example 5, no substantially uniform coating is formed as shown in Evaluation Example 2, and further, referring to Table 1, the initial charge capacity / initial discharge capacity and initial efficiency are greatly deteriorated compared to Comparative Example 4. Accordingly, when a substantially uniform coating in the form of a shell surrounding (e.g., surrounding) the core is not formed, the initial charge capacity and initial discharge capacity of the rechargeable lithium battery cell deteriorate, while the resistance increases, and the high temperature cycle life characteristics also deteriorate or are not improved.

[0213] On the other hand, in Comparative Example 6 using an increased Al coating content (eg, amount) of about 3 mol% and the same base material and coating method as the embodiment, the initial discharge capacity was significantly reduced, and the initial charge capacity and initial efficiency were also deteriorated.

[0214] In the present disclosure, "not including one or any component", "excluding one or any component", "containing no component", etc. means that the component is not added, selected or utilized as a component in the composition or compound, but due to other impurities and / or external factors, less than an appropriate amount of the component may still be included.

[0215] The battery management system (BMS) device according to the embodiment of the present invention described herein, and / or any other related device or component may be implemented using any appropriate hardware, firmware (e.g., a dedicated integrated circuit), software, or a combination of software, firmware, and hardware. For example, the various components of the device may be formed on an integrated circuit (IC) chip or on separate IC chips. Further, the various components of the device may be implemented on a flexible printed circuit film, a tape carrier package (TCP), or a printed circuit board (PCB), or formed on a substrate. Further, the various components of the device may be processes or threads that run on one or more processors in one or more computing devices, execute computer program instructions, and interact with other system components for performing various functions described herein. The computer program instructions are stored in a memory that may be implemented in a computing device using a standard storage device, such as, for example, a random access memory (RAM). The computer program instructions may also be stored in other non-temporary computer-readable media, such as, for example, a CD-ROM, a flash drive, etc. Moreover, it should be recognized by those skilled in the art that the functions of various computing devices may be combined or integrated into a single computing device, or the functions of a particular computing device may be distributed on one or more other computing devices without departing from the scope of the present disclosure.

[0216] In the present disclosure, when a particle is spherical, “diameter” indicates a particle diameter or an average particle diameter, and when a particle is non-spherical, “diameter” indicates a major axis length or an average major axis length.

[0217] In the present disclosure, "not including one or any component", "excluding one or any component", "containing no component", etc. means that the component is not added, selected or utilized as a component in the composition / structure, but due to other impurities and / or external factors, the component may still be included in less than an appropriate amount.

[0218] Although the present disclosure has been described in conjunction with what are presently considered to be practical example embodiments, it should be understood that the present disclosure is not limited to the disclosed embodiments. Instead, it is intended to cover one or more suitable modifications and equivalent arrangements included within the spirit and scope of the appended claims and their equivalents.

Claims

1. A positive electrode active material comprising: A core particle comprising a lithium nickel manganese aluminum composite oxide, and a coating on the surface of the core particle and comprising aluminum, wherein the nickel content of the core particles is 60 mol % to 80 mol % and the aluminum content of the core particles is 1 mol % to 3 mol % based on 100 mol % of the total metals other than lithium in the positive electrode active material, and Wherein, based on 100 mol % of the total metals other than the lithium in the positive electrode active material, the aluminum content of the coating layer is 0.1 mol % to 2 mol %.

2. The positive electrode active material according to claim 1, wherein The aluminum content of the coating layer is 0.5 mol % to 1.5 mol % based on 100 mol % of the total metals other than the lithium in the positive electrode active material.

3. The positive electrode active material according to claim 1, wherein The coating is in the form of a shell that continuously surrounds the entire surface of the core particle.

4. The positive electrode active material according to claim 1, wherein The thickness of the coating is 30nm-200nm.

5. The positive electrode active material according to claim 1, wherein The coating layer has a thickness variation of 20% or less in one positive electrode active material particle.

6. The positive electrode active material according to claim 1, wherein The coating layer includes an aluminum compound having a layered structure.

7. The positive electrode active material according to claim 1, wherein The coating includes LiAlO2.

8. The positive electrode active material according to claim 1, wherein The coating further includes nickel, manganese, or a combination thereof.

9. The positive electrode active material according to claim 1, wherein The lithium nickel manganese aluminum composite oxide of the core particle is represented by Chemical Formula 1: Chemical formula 1 Li a1 Ni x1 Mr y1 Al z1 M 1 w1 O 2-b1 X b1 , in, In Chemical Formula 1, 0.9≤a1≤1.8, 0.6≤x1≤0.8, 0.1≤y1≤0.39, 0.01<z1≤0.03, 0≤w1≤0.29, 0.9≤x1+y1+z1+w1≤1.1, and 0≤b1≤0.1, M 1 is one or more elements selected from B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W and Zr, and X is one or more elements selected from F, P and S.

10. The positive electrode active material according to claim 1, wherein The concentration of aluminum in the core particles is uniform.

11. The positive electrode active material according to claim 1, wherein The lithium nickel manganese aluminum composite oxide of the core particle is a compound that does not contain cobalt.

12. The positive electrode active material according to claim 1, wherein The cobalt content is 0 mol % to 0.01 mol % based on 100 mol % of total metals other than lithium in the positive electrode active material.

13. The positive electrode active material according to claim 1, wherein The core particle is in the form of a secondary particle prepared by aggregating a plurality of primary particles.

14. The positive electrode active material according to claim 13, wherein The positive electrode active material further includes a grain boundary coating portion on the surface of the primary particle inside the secondary particle and including aluminum.

15. The positive electrode active material according to claim 14, wherein The grain boundary coating portion includes an aluminum compound having a layered structure.

16. The positive electrode active material according to claim 14, wherein The grain boundary coating portion includes LiAlO2.

17. The positive electrode active material according to claim 14, wherein The grain boundary coating portion further includes nickel, manganese, or a combination thereof.

18. The positive electrode active material according to claim 14, wherein The aluminum content in the grain boundary coating portion is smaller than the aluminum content in the coating layer.

19. The positive electrode active material according to claim 1, wherein The average particle size D50 of the positive electrode active material is 10 μm to 18 μm.

20. The positive electrode active material according to claim 1, wherein The positive electrode active material does not include sodium.

21. A method for preparing a positive electrode active material, the method comprising: Mixing a nickel-manganese-aluminum composite hydroxide and a lithium raw material and performing a first heat treatment to obtain a lithium-nickel-manganese-aluminum composite oxide; as well as The obtained lithium nickel manganese aluminum composite oxide is added to and mixed with a solution of an aqueous solvent of an aluminum raw material, dried and subjected to a second heat treatment to obtain a positive electrode active material, wherein based on 100 mol % of total metals in the nickel-manganese-aluminum composite hydroxide, the nickel content is 60 mol % to 80 mol % and the aluminum content is 1 mol % to 3 mol %, and Wherein, based on 100 mol % of total metals other than lithium in the positive electrode active material, the aluminum content in the aluminum raw material is 0.1 mol % to 2 mol %.

22. The method according to claim 21, wherein The aluminum content in the aluminum raw material is 0.5 mol % to 1.5 mol % based on 100 mol % of total metals other than lithium in the positive electrode active material.

23. The method according to claim 21, wherein The aluminum raw material includes aluminum nitrate, aluminum sulfate, aluminum carbonate, aluminum hydroxide or a combination thereof.

24. The method according to claim 21, wherein The pH of the aqueous solvent solution of the aluminum raw material is 1.5 to 3.

5.

25. The method of claim 21, wherein The obtained lithium nickel manganese aluminum composite oxide is added to the aqueous solvent solution of the aluminum raw material and mixed with the aqueous solvent solution of the aluminum raw material for 5 to 80 minutes, and the pH of the solution obtained after mixing is 4.5 to 8.

5.

26. The method of claim 21, wherein Drying is performed at 40°C to 240°C.

27. The method of claim 21, wherein The first heat treatment is performed at 750°C to 950°C, and The second heat treatment is performed at 700°C to 850°C.

28. A positive electrode comprising: positive electrode current collector; and a positive electrode active material layer on the positive electrode current collector, The positive electrode active material layer comprises the positive electrode active material according to any one of claims 1 to 20 or the positive electrode active material prepared by the method according to any one of claims 21 to 27.

29. The positive electrode according to claim 28, wherein The loading level of the positive electrode active material layer is 10 mg / cm 2 ~40mg / cm 2 .

30. The positive electrode according to claim 28, wherein The positive electrode active material layer has a density of 3.3 g / cc to 3.7 g / cc.

31. A rechargeable lithium battery comprising: The positive electrode according to any one of claims 28 to 30; Negative electrode; and Electrolyte.

32. The rechargeable lithium battery of claim 31, wherein The charging voltage of the rechargeable lithium battery is greater than or equal to 4.45V.